Evaluation of asthmatic patient dyspnea in asthma center at Baghdad city - Ali Khamies Aliwie; Aqeel Habeeb Jasim (Journal of Education and Health Promotion)
BACKGROUND: Asthma was a heterogeneous condition, with dyspnea during exercise affecting individuals to a variable degree. The research aims to evaluate dyspnea in an asthmatic patient and to find out the relationship between dyspnea and sociodemographic variables. MATERIALS AND METHODS: A cross-sectional study that included 130 patients with asthma in an asthma center in Baghdad City, Iraq was conducted to assess asthmatic patient dyspnea. From 1st September to December 20, 2023, we recruited a total of 130 patients attending outpatient respiratory clinics from three teaching hospitals and centers located in Baghdad, Iraq, the current study used purposive sampling. Data were collected through a pretested self-administered questionnaire. Collected data were coded and put into SPSS Statistics (v25). Inferential and descriptive statistical procedures were conducted. Percentages and frequencies for every item within the asthmatic patient were measured. The mean score attained from the scale was used to measure the subject. RESULT: The data reveals that most participants consistently reported experiencing high levels of dyspnea, with a Mean + SD (37.13 ± 8.06). These responses, indicate severe levels of asthma according to their assessment, signifying a prevalent occurrence of this symptom among the respondents. The study shows a highly significant relationship between occupation, education, and smoking with dyspnea at a P value of 0.05. CONCLUSION: The results show that the majority in the sample had a severe level of dyspnea, the study shows a highly significant relationship between occupation, education, and smoking with dyspnea at P value of 0.05.